2023
DOI: 10.1242/jeb.246304
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to acute warming at the agitation temperature in a temperate shark

Ian A. Bouyoucos,
Alyssa M. Weinrauch,
Ken M. Jeffries
et al.

Abstract: Thermal tolerance and associated mechanisms are often tested via the critical thermal maximum (CTMax). The agitation temperature is a recently described thermal limit in fishes that has received little mechanistic evaluation. The present study used a temperate elasmobranch fish to test the hypothesis that this thermal tolerance trait is partially set by the onset of declining cardiorespiratory performance and the cellular stress response. Pacific spiny dogfish (Squalus suckleyi) were screened for cardiorespira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…The agitation temperature of 22.0 ± 1.4 °C from this study falls within this expected range, and the activation of several genes at the agitation treatment temperature, suggests that a shift in the cellular response to temperature occurs at the onset of thermal avoidance behaviour. Similar results were observed in Pacific spiny dogfish ( Squalus suckleyi ) where they showed a cellular stress response occurred at the agitation temperature (Bouyoucos et al, 2023). Morrison et al (2020) showed that CT max generally increased with acclimation temperature in Brook Trout, however, CT max plateaued at acclimation temperatures above 20 °C that coincided with a decrease in hepatosomatic index, and an increase in plasma lactate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The agitation temperature of 22.0 ± 1.4 °C from this study falls within this expected range, and the activation of several genes at the agitation treatment temperature, suggests that a shift in the cellular response to temperature occurs at the onset of thermal avoidance behaviour. Similar results were observed in Pacific spiny dogfish ( Squalus suckleyi ) where they showed a cellular stress response occurred at the agitation temperature (Bouyoucos et al, 2023). Morrison et al (2020) showed that CT max generally increased with acclimation temperature in Brook Trout, however, CT max plateaued at acclimation temperatures above 20 °C that coincided with a decrease in hepatosomatic index, and an increase in plasma lactate.…”
Section: Discussionsupporting
confidence: 80%
“…Studies that assess thermal endpoints can provide a general understanding of when fish display a behavioural reaction to a thermal threshold, however, such studies do not provide insight into sub-organismal responses of the fish. Despite the potential utility of identifying behavioural avoidance responses to thermal stress in fishes, relatively little is known about the physiological mechanisms that coincide with the agitation temperature in fishes (Bouyoucos et al 2023).…”
Section: Introductionmentioning
confidence: 99%